2007
DOI: 10.1080/09523980701680854
|View full text |Cite
|
Sign up to set email alerts
|

E‐Learning in a Mega Open University: Faculty attitude, barriers and motivators

Abstract: In the distance teaching institutions where e-learning initiatives are underway and where the planners and administrators grapple with effective adoption and deployment of technology-enabled education, faculty attitude and motivation assume considerable significance. Attitudinal pre-dispositions and institutional and allied barriers (including appropriate policy initiatives) are assumed to play a crucial role in making an effective shift from traditional distance education delivery to web-enabled education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 22 publications
10
143
1
6
Order By: Relevance
“…Several previous studies have mixed views regarding this, Teo [42], Teo, Lee, & Chai [37], Panda, & Mishra [102] indicated that facilitating conditions might have influence on the adoption of new technologies, while Pynoo et al [101] showed that facilitating conditions had no impact on intention to use ICT by teachers, rather it affected the actual use. As found in the qualitative interviews, the facilitating conditions for the schools in this study were poor.…”
Section: H Facilitating Conditions and Behavioural Intention To Use mentioning
confidence: 92%
“…Several previous studies have mixed views regarding this, Teo [42], Teo, Lee, & Chai [37], Panda, & Mishra [102] indicated that facilitating conditions might have influence on the adoption of new technologies, while Pynoo et al [101] showed that facilitating conditions had no impact on intention to use ICT by teachers, rather it affected the actual use. As found in the qualitative interviews, the facilitating conditions for the schools in this study were poor.…”
Section: H Facilitating Conditions and Behavioural Intention To Use mentioning
confidence: 92%
“…Panda & Mishra (2007) Faculty were less satisfied with teaching online when they had technical problems.…”
Section: Resultsmentioning
confidence: 99%
“…In more recent literature, many of the same themes appear. Reasons cited for resistance to adoption relate to workload, lack of experience, accessibility, connectivity, and lack of institutional infrastructure to support e-learning (Allen & Seaman, 2006;Bolliger & Wasilik, 2009;Cook, Ley, Crawford, & Warner, 2009;Georgina & Olson, 2008;Kennedy, Jones, Chambers & Peacock, 2011;Panda & Mishra, 2007;Ward, Peters & Shelley, 2010).…”
Section: E-learning: the Faculty Perspectivementioning
confidence: 99%